(untitled) (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the frequency of multi-drug-resistant tuberculosis in patients with pulmonary tuberculosis. METHODOLOGY: This cross-sectional investigation was executed in the year 2024 within the Department of General Medicine and Pulmonology at Ghulam Muhammad Mahar Medical College (GMMMC), situated in Sukkur, encompassing a cohort of 147 patients who received a diagnosis of pulmonary tuberculosis (PTB) and exhibited a clinical history of symptoms enduring for a period surpassing 2 weeks. Eligible subjects, whose ages ranged from 18 to 70 years and inclusive of individuals of both sexes, were methodically assessed to examine the prevalence of multi-drug-resistant tuberculosis (MDR-TB) among patients diagnosed with pulmonary tuberculosis. The amassed dataset underwent comprehensive analysis employing SPSS version 26, which incorporated both descriptive and inferential statistical methodologies. RESULTS: Multidrug-resistant tuberculosis (MDR-TB) was detected in 61 out of 147 patients diagnosed with pulmonary tuberculosis, resulting in a prevalence rate of 41.49%. Among the individuals diagnosed with MDR-TB, an overwhelming 96.7% fell within the age range of 18 to 40 years, and 68.9% were identified as male. Statistically significant correlations were established with respect to age (p=0.000), gender (p=0.000), educational attainment (p=0.020), employment status (p=0.001), socioeconomic status (p=0.037), marital status (p=0.001), and tobacco use (p=0.009). CONCLUSION: This study revealed a notably high frequency of multidrugresistant tuberculosis (MDR-TB) among patients with pulmonary tuberculosis (PTB). The findings highlight significant associations between MDR-TB and key demographic and socioeconomic factors, including younger age, male gender, lower educational status, and smoking habits. These findings highlight the need for improved diagnostic screening, especially molecular testing like GeneXpert, and targeted interventions in high-risk populations. To reduce MDR-TB in this region, early detection, treatment adherence, and socioeconomic disparities need to be improved.